Impacts of Goat Horn/Ammonium Polyphosphate on Mechanical and Thermal Properties of Epoxy Composites - N. Parkunam; P. Gopal; G. Navaneethakrishnan; R. Palanisamy; Beena Stanislaus Arputharaj; C. Ahamed Saleel; Qasem M. Al‐Mdallal (Engineering Reports)
ABSTRACT In this paper, the ammonium polyphosphate (APP) is mixed with epoxy to fabricate APP/epoxy goat horn composites. The composites were obtained by casting method with different weight ratios of APP of 0%, 10%, 15%, and 20% for improving the mechanical and thermal properties. This is the first paper to discuss about both mechanical and thermal properties of APP/epoxy goat horn composites. The mechanical properties were evaluated by tensile test and wear test. For the goat horn composites with a content of 20 wt% of APP, the tensile strength was 30 MPa, shows that adding APP led to composites having a better tensile strength. From limiting oxygen index test results, it is clear that goat horn composite is fire retardant, and that the fire‐retardant value improves with the addition of APP up to a weight ratio of 15% APP. The thermogravimetric analysis (TGA) reveals that the degradation of composites in relation to temperature. From the TGA analysis, the bio composites without APP gives the better results comparing with incorporation of APP in composites up to 40% of weight loss. At the same time, the 50% of weight loss occur at the degradation temperature of around 380°C for 20 wt% of APP composites. It shows the addition of APP improves the thermal stability of the composites. The ignition time from the horizontal flammability test of the composites of 0, 10, 15, and 20 wt% APP were 20, 22, 24, and 25 (in s) respectively. It shows that the addition of filler material into the composites, the ignition time also increases. The water absorption percentage was peak at 15% of APP and lower at 10% of APP. All the samples were saturated after 80 h. The lower percentage of water absorption in composites can be attributed to the improved interfacial bonding between the fibers and matrix. From scanning electron microscopy (SEM) analysis the morphological structure and dispersion of ammonium polyphosphate and goat horn particles in epoxy bio composites were studied.